Sustainable Marketing: Market-Driving, Not Market-Driven - Sheth, Jagdish N.; Parvatiyar, Atul (Journal of macromarketing, 2021)
Sustainability has emerged as a critical macromarketing perspective over the last five decades. Starting with the early concerns in the 1960s about the world’s finite resources that would limit economic growth, sustainability thinking has expanded to encompass societal issues and ecological and environmental considerations in economic and governance activities. Governments and businesses need to act in tandem to address myriad world problems associated with climate change, pollution, environmental degradation, depleting resources, and the socio-economic disparities that characterize persistent world hunger and poverty. A vital aspect of this challenge is to stop or reverse unsustainable production and consumption that have hitherto been pursued as part of market-driven business activity. Marketing, through its market-driven consumption-oriented practices, may have knowingly or unknowingly promoted these unsustainable production-consumption practices. Therefore, it needs to change its orientation from merely being responsive to consumer and market needs into a more responsible approach that drives markets for sustainable products and services and builds sustainable societies. In this paper, we review how sustainable marketing considerations have grown but not to the extent of becoming the driver of markets and business practices that meet sustainability goals. To this end, we present a framework for driving sustainable consumption through corporate marketing strategy and relevant government interventions. We highlight four strategies of corporate marketing and four types of government intervention for sustainable marketing.